Black Fungus: a rising consternation among COVID patients presented in tertiary care hospital in Islamabad-PIMS - Khan, Manza Maqsood; Syed Ansab Hasnain; Altaf Hussain; Malik Jawad Faisal (Journal of the Pakistan Medical Association, 2022)
For almost one and a half year the world is facing the pandemic called COVID-19, which is an acute respiratory distress syndrome caused by coronavirus 2 (SARS-CoV2). This disease has already engulfed many lives and has not been tamed so far. Physicians all over the world still, trying to get a hold of this global health issue, are faced with another life-threatening challenge associated with COVID-19, called black fungus-Mucormycosis. Within a span of few weeks, we have encountered three cases of black fungus in our institute which has stirred a serious concern among physicians in Pakistan. Keywords: Mucormycosis, Black fungus, COVID-19, Pandemic.